Public participation in environmental impact assessment of Klang Valley mass rapid transit, Sungai Buloh-Kajang line in Malaysia - Waliyu, Aiyeola Abiola (2014)
The purpose of this study was to assess the level of public participation within the context of Environmental Impacts Assessment (EIA) procedure using the Klang Valley rapid transits as a case study. The study examined the effect of public attitude, motivation, access to information, EIA policy, practice and performance on public participation. Based on the empirical study, the study used access to information as a mediating variable between other independent variables and the dependent variable. A quantitative method was employed to collect data on the population of the people who are living along the receptive area of the project. A set of questionnaire was used to obtain information for this study. The content of the questionnaire was divided into four parts. Part A was for the demographic information on the respondents, part B was for the effect of attitude, access to information and motivation on public participation. Part C was to determine the effectiveness of EIA policy, practice and performance and its relationship with public participation. The last part of the questionnaire was to determine the awareness of the EIA of the project and level at which the public participate using sherry Arntein’s ladder of public participation. In order to analyse the data collected, structural equation model (SEM) was used while descriptive statistics methods were used for Part A and Part D of the questionnaire. The results showed that attitude, access to information and motivation have significant effect on public participation. The results also showed that access to information mediates significant positively between attitude, motivation and public participation. The results equally revealed the relationship between EIA policy, practice and public participation as mediated by access to information to be positive. On the other hand, EIA performance has direct relationship with public participation without any mediation and it was significant whereas, when mediated with access to information it was not significant. Lastly, the result also showed that out of 304 respondents, 29.3 % (n=89) said they are aware about the EIA whereas 70.7 % (n=215) said they did not know about it. It was equally observed that 54% (N=164) among 304 respondents believed that their participation fell within the level of manipulation and therapy, while 34% (N=104) of the respondents believed their participation could be rated between information and placation. The last group of 12% (N=36) of the respondents believed that their participation could be rated within partnership and citizen control. Going by the finding of this study, it was revealed that the public participation role in environmental management through EIA process still require an improvement. It was observed that access to information play a significant role on public participation in environmental management. It was equally revealed that the effectiveness of EIA policy, practice and performance can be measured through public participation because of the significant relationship that was established in the study. In conclusion, for improvement of public interest and participation, the study recommended an establishment of an integrated environmental information system awareness unit (IEISA) which will in turn manage a simplified information web based platform for the public, professional as well as consultants using the same database.